5(5+t)-3(t-6)=

Simple and best practice solution for 5(5+t)-3(t-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5+t)-3(t-6)= equation:


Simplifying
5(5 + t) + -3(t + -6) = 0
(5 * 5 + t * 5) + -3(t + -6) = 0
(25 + 5t) + -3(t + -6) = 0

Reorder the terms:
25 + 5t + -3(-6 + t) = 0
25 + 5t + (-6 * -3 + t * -3) = 0
25 + 5t + (18 + -3t) = 0

Reorder the terms:
25 + 18 + 5t + -3t = 0

Combine like terms: 25 + 18 = 43
43 + 5t + -3t = 0

Combine like terms: 5t + -3t = 2t
43 + 2t = 0

Solving
43 + 2t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-43' to each side of the equation.
43 + -43 + 2t = 0 + -43

Combine like terms: 43 + -43 = 0
0 + 2t = 0 + -43
2t = 0 + -43

Combine like terms: 0 + -43 = -43
2t = -43

Divide each side by '2'.
t = -21.5

Simplifying
t = -21.5

See similar equations:

| x(5x+1)(x-9)=0 | | 3(2n-7)+7(4-2n)= | | x^2-6x+20=0 | | 124-6x=21x+16 | | 3/2(5x-2)=x | | 3(x+4)+2(5x+2)= | | 6x+7+3x+1= | | -4x+5=5-4x | | -3y+6=-4y+7 | | 7xy-xy+3xy= | | 4w-5+9w+2= | | -4+5=5-4x | | 20-x=10x-2 | | 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 | | -14-4x=13-7x | | 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= | | 6(6v+6)=1+6v | | 12-8x=39-15x | | 2t+11t=104 | | 6x+7=-199-8x | | 14=20-2x | | 30k+10=18k+22 |

Equations solver categories